Analysis of transplant rejection in rabbits aponeurosis - Andre Ibrahim David; Eduardo Sauerbronn Gouvea; Felipe Ribeiro Batista; Paulo Henrique Fogaça de Barros; Dino Martini Filho; Victor Arias; Paulo Roberto Corsi; Luiz Arnaldo Szutan (Einstein (São Paulo), 2012)
Objective: To study the feasibility of heterologous aponeurosisto close the abdominal wall of rabbits emphasizing the rejectionprocess. Methods: This project was approved by the Animals CareCommittee of the Faculdade de Ciências Médicas da Santa Casa deSão Paulo, and it was carried out at the Experimental Surgery andTechnical Unit. Four red female rabbits exchanged abdominal wallaponeurosis with other four white male animals. Two rabbits justhad it removed and replaced to be the control group for the healingprocess. Animals were evaluated once a day, and after 7 days theywere sacrificed. Immunohistochemical analysis with CD20 and CD79was done. Results: The animals did not have cellulitis, abscess,hematoma, wound dehiscence or herniation. The graft site showedintense hyperemia. The histological analysis showed an inflammatoryprocess with maturing myofibroblasts and collagen ranging fromincipient to moderate. The number of vessels was reduced and theinflammatory cells were most plasma cells and macrophages. Therewere no morphological signs of acute rejection with aggressivevascular endothelial damage. The adjacent muscle showed signsof degeneration with inflammatory centralization of nuclei andcytoplasmic condensation. The immunohistochemical analysis (CD20and CD79) showed that the inflammatory process was not mediatedby lymphocytes. Mann-Whitney nonparametric test showed thatthe hypothesis of equality (p>0.05) should not be discarded.Conclusion: There were no postoperative complications (fistulas,dehiscence etc.) and the histological analysis showed nonspecificinflammatory process. The immunohistochemical analysis showedthat the inflammatory process was not due to a possible rejection.